Antioxidant effect of thyme ( -L.) and oregano ( -L.) extracts in soybean oil under thermoxidation - Jorge, Neuza [UNESP]; Veronezi, Carolina Médici [UNESP]; Ré, Patrícia Vierira Del [UNESP] (Wiley, 2014)
The rancidity of vegetable oils is considered one problem in the food industry,thus, are added antioxidants in food. The objective of this study was to investigatethe antioxidant effect of oregano and thyme extracts in soybean oil underthermoxidation. Soybean oil containing 3,000 mg/kg of oregano and thyme oleo-resins and the mixture of both, as well as soybean oil containing tert-butylhydroquinone (TBHQ; 50 mg/kg) and soybean oil free of were subjected tothermoxidation. Then, the physicochemical properties and fatty acid profile wereevaluated. Oregano and thyme oleoresins applied separately presented a higherprotective effect, inhibiting a greater formation of polar compounds than the anti-oxidant TBHQ, indicating that the addition of 3,000 mg/kg has ensured a betteroxidative protection than the synthetic antioxidant. The increase in the concentra-tion of oleoresins by mixing thyme and oregano extracts has given a higher pro-tective effect.
Keywords: especiarias; termoxidação; atividade antioxidante